Implicit Bias in Deep Linear Classification: Initialization Scale vs Training Accuracy - Moroshko, Edward; Gunasekar, Suriya; Woodworth, Blake; Lee, Jason; Srebro, Nati; Soudry, Daniel (NeurIPS 2020, 2020)
See full publication in the "View Publication" link.